POSSIBILITIES OF THE STEEL SURFACE REMELTING RESULTS EVALUATION - CHMELÍČKOVÁ, Hana; ŘIHÁKOVÁ, Lenka (Trends in education, 2018)
Laser surface remelting is one of the technologies utilizing laser energy to create a thin surface layer on the unaffected material, which then has a higher resistance (Dahotre & Hamikar, 2008). Although it is application mainly for continuous lasers, this process can be carried out on a pulsed laser where the melted area is created by dense overlapping of individual pulses. Traces 15 mm long were consequently created on steel samples, the variable parameter being the distance of the sample surface from the focal plane of the laser beam with which the power density was changed. Already during the visual observation of the experiment, it was obvious that with its decrease the width of the trace increased, but at the same time the temperature of the melt dropped. For the evaluation of the samples, the students used a desktop digital microscope, on which it is possible to interactively measure the width of the tracks and to save the photographs for further processing. After cross section cuts were made, the depths of the remelting areas were measured and displayed on the laser scanning confocal microscope. The development of the transverse and longitudinal profiles was evaluated by a contact probe.
Keywords: laser; surface remelting; digital and confocal microscope; contact profilometer